Judith Rebecca von Wrbna and Maria Sophia von Dietrichstein: Two Imperial Ambassadresses from the Kingdom of Bohemia at the Court of Madrid (1653–1674) (Theatrum historiae, 2017)
This article focuses on the diplomatic activity of two ambassadors’s wives from the Kingdom of Bohemia at the court of Madrid between (1653–1674). In that time, the spouse of a diplomat was called “ambassadress”. Throughout the 17th century, the ambassadresses acquired ceremonial, political and social functions. The Countess of Lamberg and the Countess of Pötting were ambassadresses during a special period: during their ‘embassies’, the “Question of the Succession” marked the Hispanic monarchy relations with the Holy Roman Empire; and a Habsburg Queen, Mariana of Austria, was consort (and after regent) of Spain. Also, the second half of the 17th century coincided with the consolidation of the role of the ambassadresses at European courts. Judith Rebecca Wrbna and Maria Sophia von Dietrichstein paved the way for their successor, set precedents and made it easier for subsequent Imperial ambassadresses to access the diplomatic areas of the Spanish court. At the same time, both ambassadresses helped gain acceptance and legitimacy for the political actions of the ambassadors in court circles, established a good relation with the Queen Mariana of Austria, achieved their ceremonial and social duties (visiting), and acted as brokers at court. In short, these two ambassadresses marked a turning point in the diplomatic life of the following Imperial ambassadresses to Spain.
Keywords: Ambassadresses; 17th century; diplomacy; courts of Madrid; Holy Roman Empire